Unified Approach to Fused and Spirocyclic Oxindoles through Lewis‐Acid‐Promoted Opening of Spiroepoxyoxindoles with Allylsilanes: Application to the Formal Synthesis of (±)‐Physovenine. Issue 18 (10th May 2017) - Sharma, Brijesh M.; Yadav, Mahesh; Gonnade, Rajesh G.; Kumar, Pradeep
Abstract : A protocol for the construction of oxindoles containing all‐carbon quaternary centres in a highly regioselective manner has been developed. The reaction involves opening of spiroepoxyoxindoles with allylsilanes to give Hosomi–Sakurai‐type products as well as new silicon‐containing spirocyclic oxindoles. A formal synthesis of (±)‐physovenine was accomplished in five steps using this protocol. Abstract : A method for the C‐3 functionalization of 2‐oxindoles through the Lewis‐acid‐promoted opening of spiroepoxyoxindoles with allylsilanes to give Hosomi–Sakurai‐type products as well as spirocyclic oxindoles with all‐carbon quaternary centres has been developed. A formal synthesis of (±)‐physovenine was accomplished in five steps using this approach.